Review of electrophysiological models to study membrane potential changes in breast cancer cell transformation and tumor progression - Mahapatra, Chitaranjan; Kishore, Arnaw; Gawad, Jineetkumar; Al-Emam, Ahmed; Kouzeiha, Riad Azzam; Rusho, Maher Ali (Frontiers in Physiology, 2025)
The transformation of normal breast cells into cancerous cells is a complex process influenced by both genetic and microenvironmental factors. Recent studies highlight the significant role of membrane potential (Vm) alterations in this transformation. Cancer cells typically exhibit a depolarized resting membrane potential (RMP) compared to normal cells, which correlates with increased cellular activity and more aggressive cancer behavior. These RMP and Vm changes are associated with altered ion channel activity, altered calcium dynamics, mitochondrial dysfunction, modified gap junction communication, and disrupted signaling pathways. Such fluctuations in RMP and Vm influence key processes in cancer progression, including cell proliferation, migration, and invasion. Notably, more aggressive subtypes of breast cancer cells display more frequent and pronounced Vm fluctuations. Understanding the electrical properties of cancer cells provides new insights into their behavior and offers potential therapeutic targets, such as ion channels and Vm regulation. This review synthesizes current research on how various factors modulate membrane potential and proposes an electrophysiological model of breast cancer cells based on experimental and clinical data from the literature. These findings may pave the way for novel pharmacological targets for clinicians, researchers, and pharmacologists in treating breast cancer.